RANCANG BANGUN SISTEM INFORMASI BADAN USAHA MILIK DESA ( BUMDES ) BERBASIS WEB MOBILE - Asep Afandi Afandi (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2020)
The information system of village-owned enterprises is still done manually, and in delivering information to the people in the village of Sidokayao, Abung Tinggi Subdistrict, North Lampung Regency, so that some people do not know about Sidokayo Village, there are bumdes activities, therefore, an application must be designed using internet facilities that can used by the public in accessing information and can save time, thus in Sidokayo village a website application is needed.With the existence of a mobile web-based village-owned enterprise information system it is hoped that it can facilitate access to information and improve services in marketing businesses in the Sidokayo village managed by BUMDes.